Porting process model for mobile application - Rajadorai @ Rajoo, Kesava Pillai (2017)
The current trend of Information and Communication Technology (ICT) is the convergence of communication, computing and the Internet. The birth of 3rd Generation mobile phone standard (3G) contributed to the development of smartphones. In the view of this trend, the mobile application development companies are developing different kind and type of applications to use in these smartphones. As these smartphones have different brands and models, it becomes an issue for the developers to develop an application that runs on any smartphones. Developers are also finding difficulties to port the native applications to other platform due to lack of standard porting process. This thesis analyzes the issues in mobile application porting processes and proposes a process model for mobile application porting. This process model is timely as the existing software development process models could not able to cater a specific guideline during mobile application porting. The research methodology used in this research composed of four phases; Literature Review, Preliminary Study, Design Proposed Model and Evaluation Proposed Model and were sequentially executed. To ensure legality, accuracy, reliability and validity of the research, some ethical considerations, quality of sample data collected and data sources were considered. The proposed process model composed of eight (8) processes, namely: Feasibility Analysis, Porting Requirement, Gaps Analysis, Porting Specification, Porting Design, Porting, Ported Mobile Application Testing and Test Report verification. Each of the processes were discussed in detail to provide comprehensive guidelines for the developers. A case study based porting assignment has been created (i.e. An Android application was ported to Windows Mobile 8.0 platform) to evaluate the effectiveness and efficiency of the proposed process model. Initially the porting assignment and proposed process model were reviewed by the experts. Finally, to justify the creditability of the proposed process model, Static-Group Comparison study was used. The data was collected from the comparison of two groups (i.e. Ad-Hoc and Treated), and then quantitatively evaluated. The overall finding shows that the proposed process model possesses most disciplined tasks where clear instruction were given throughout their porting process. Therefore, porting activities can be optimized and all necessary activities can be clearly identified and controlled. Thus, the proposed process model has greatly help the developers to complete the porting project within costs and time, as well improves the quality of the application.